1997
DOI: 10.1530/eje.0.1370048
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin concentration before and during testosterone replacement in primary hypogonadic men

Abstract: Objective: To study circadian levels of melatonin in primary hypogonadic adult men before and after testosterone treatment. Design and methods: Circadian serum melatonin profiles were studied in six men with primary hypogonadism before and during testosterone substitution and compared with an age-matched control group (n ¼ 6). Results: Hypogonadal patients had higher plasma melatonin concentrations than the control group during day time (34:2 Ϯ 8:8 compared with 5:4Ϯ 0:5 ng/l, means Ϯ S.D.; P < 0:005) and nigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 22 publications
1
11
0
Order By: Relevance
“…Human studies indicate that decreased concentrations of circulating melatonin (such as those brought about by circadian disruption) can result in increased release of the gonadotropins luteinizing hormone and follicle-stimulating hormone from the pituitary and estrogen release by the ovaries (21)(22)(23)(24)(25). There is also evidence from clinical studies of a relationship between melatonin and male reproductive hormones (26)(27)(28)(29). Thus, through its control over gonadal hormone production, melatonin may have an inhibitory effect on hormone-dependent tumors.…”
Section: Cancer Epidemiol Biomarkers Prev 2008;17(12) December 2008mentioning
confidence: 99%
“…Human studies indicate that decreased concentrations of circulating melatonin (such as those brought about by circadian disruption) can result in increased release of the gonadotropins luteinizing hormone and follicle-stimulating hormone from the pituitary and estrogen release by the ovaries (21)(22)(23)(24)(25). There is also evidence from clinical studies of a relationship between melatonin and male reproductive hormones (26)(27)(28)(29). Thus, through its control over gonadal hormone production, melatonin may have an inhibitory effect on hormone-dependent tumors.…”
Section: Cancer Epidemiol Biomarkers Prev 2008;17(12) December 2008mentioning
confidence: 99%
“…(1988), Ozata et al. (1996) and Rajmil et al. (1997), who found increased melatonin secretion in patients with hypergonadotropic hypogonadism.…”
Section: Discussionmentioning
confidence: 99%
“…The data of serum melatonin levels in primary hypogonadism are controversial and more studies are needed to clarify this issue. Luboshitzky et al (1996Luboshitzky et al ( , 1997 found low melatonin levels in primary hypogonadism, whereas Tortosa et al (1988) and Rajmil et al (1997) reported increased serum melatonin levels in primary hypogonadism.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Okatani et al [1999] showed that the increase in melatonin synthesis in a perimenopausal period in female rats might originate in the decreased levels of an endogenous estrogen. The effect of male sex hormones on melatonin level has not been thoroughly understood; however, it has been shown that under some pathological conditions the deficit of male hormones leads to an abnormal increase in melatonin level, while treatment with testosterone normalizes them [Luboshitzky et al, 1996;Rajmil et al, 1997]. It has been suggested that testosterone affects melatonin level by modulating its metabolism [Caglayan et al, 2001].…”
Section: Discussionmentioning
confidence: 99%